PENDIDIKAN KESEHATAN: TENTANG PENTINGNYA DONOR DARAH SEBAGAI WUJUD KEPEDULIAN TERHADAP SESAMA DI SMK DARUL MA'ARIF JAKARTA - Imelda , Ria Ika; Juri Sri Ayu; Shilvia Dwi Kristanti; Zhaliatul Khomariah (Bengkulu Institute, 2025)
Blood donation is an activity of donating blood, both for replacement blood needs and as a direct donor, which has an important function in various health services. The death rate due to unavailability of blood reserves in developing countries is relatively high. This community service activity aims to assist the Indonesian Red Cross (PMI) in collecting and socializing blood donations and as an effort to help the availability of blood stock in the city of DKI Jakarta. Apart from that, another aim is to encourage increased community awareness in social activities and realize the implementation of community service programs by lecturers at the Harum Jakarta Nursing Academy. This blood donation activity is a collaboration between Darul Ma'arif Vocational School, PMI and Akademi Keperawatan Harum Jakarta in order to help collect blood for social preparation for the community.